Measurement of the electrical quantities of the wet scrubber - Zoranović Miodrag; Ivanišević Mladen (Journal on Processing and Energy in Agriculture, 2022)
With the aim of reducing environmental, energy and quality problems in the field of farming of animal species, laboratory for agricultural technique in animal husbandry, Department of Agricultural Engineering, Faculty of Agriculture, University of Novi Sad, integrally develops a system for wet air purification, wet scrubber, and its energy control. The goal of electrical measurements in a wet scrubber is to determine instantaneous and interval-accurate values of electrical quantities, defined by physical methods. Devices for electrical measurements give precise values of basic electrical quantities: current, electromotive force, voltage, impedance, electrical work, power, and energy. Simple periodic voltages and currents are crucial for wet scrubber drive elements. They are determined by three quantities: amplitude, frequency, and phase. The paper presents the basic patterns for the measured values of wet scrubber drive elements: AC operation, AC power, AC power with active resistances in the circuit and AC power with impedance in the electric circuit. The presence of many drive elements for partial operational actions in a wet scrubber is the basic reason for choosing a central atomizer, as the object of methodologically original energy analysis of this work.